Role of ivermectin and colchicine in the treatment of COVID-19: a randomized controlled clinical trial - Hemmat Abd El-Salam Ahmed Salama; Eman El-Sayed Ahmed; Ghada Essam El-Din Amin; Mohamed Farouk Allam; Ahmed Nour El-Din Hassan; Mohamed Abd El Rahman Hassan El Shayeb (Journal of Infection in Developing Countries)
Introduction: The objective of this study was to assess the effectiveness of ivermectin and colchicine as treatment options for coronavirus disease 2019 (COVID-19).